Chemical binding of molecular‐imprinted polymer to biotinilated antibody: Utilization of molecular imprinting polymer as intelligent synthetic biomaterials toward recognition of carcinoma embryonic antigen in human plasma sample. Issue 9 (23rd March 2021) - Abdollahiyan, Parinaz; Mohammadzadeh, Arezoo; Hasanzadeh, Mohammad
Abstract: In this study, a novel biosensor based on molecular imprinting polymer (MIP) methodology was fabricated toward recognition of carcinoembryonic antigen (CEA). For this purpose, poly (toluidine blue) (PTB) was electropolymerized on the surface of gold electrode in the absence and presence of CEA. So, the target molecules were entrapped into the imprinted specific cavities of MIP. Obtained results show that, the binding affinity of the MIP system was significantly higher than that of revealed for the nonimprinted polymer (NIP) system, MIP‐based biosensor revealed linear response from (0.005 to 75 μg/L) and low limit of quantification of (0.005 μg/L) by using chronoamperometry technique, leading to CEA monitoring in real and clinical samples. Thus, a novel technique for rapid, simple, sensitive and affordable monitoring of CEA (LLOQ = 0.005 μg/L) has provided through developed biosensor. From a future perspective, moreover, this method can be considered as an applicable candidate in biomedical and clinical analysis for point‐of‐care usages.